Association of Circulating Vascular Endothelial Growth Factor Levels With Autoimmune Diseases: A Systematic Review and Meta-Analysis - Zhan, Haoting; Li, Haolong; Liu, Chenxi; Cheng, Linlin; Yan, Songxin; Li, Yongzhe (Frontiers in Immunology, 2021)
Background: Autoimmune diseases (ADs) are characterized by immune-mediated tissue damage, in which angiogenesis is a prominent pathogenic mechanism. Vascular endothelial growth factor (VEGF), an angiogenesis modulator, is significantly elevated in several ADs including rheumatoid arthritis (RA), systemic sclerosis (SSc), and systemic lupus erythematosus (SLE). We determined whether circulating VEGF levels were associated with ADs based on pooled evidence. Methods: The analyses included 165 studies from the PubMed, EMBASE, Cochrane Library, and Web of Science databases and fulfilled the study criteria. Comparisons of circulating VEGF levels between patients with ADs and healthy controls were performed by determining pooled standard mean differences (SMDs) with 95% confidence intervals (CIs) in a random-effect model using STATA 16.0. Subgroup, sensitivity, and metaregression analyses were performed to determine heterogeneity and to test robustness. Results: Compared with healthy subjects, circulating VEGF levels were significantly higher in patients with SLE (SMD 0.84, 95% CI 0.25–1.44, P = 0.0056), RA (SMD 1.48, 95% CI 0.82–2.15, P = 0.0000), SSc (SMD 0.56, 95% CI 0.36–0.75, P = 0.0000), Behcet’s disease (SMD 1.65, 95% CI 0.88–2.41, P = 0.0000), Kawasaki disease (SMD 2.41, 95% CI 0.10–4.72, P = 0.0406), ankylosing spondylitis (SMD 0.78, 95% CI 0.23–1.33, P = 0.0052), inflammatory bowel disease (SMD 0.57, 95% CI 0.43–0.71, P = 0.0000), psoriasis (SMD 0.98, 95% CI 0.62–1.34, P = 0.0000), and Graves disease (SMD 0.69, 95% CI 0.20–1.19, P = 0.0056). Circulating VEGF levels correlated with disease activity and hematological parameters in ADs. Conclusion: Circulating VEGF levels were associated with ADs and could predict disease manifestations, severity and activity in patients with ADs.